Nail changes in construction site workers: an observational study - Kamra, Nidhi; Sardana, Sahil (International Journal of Research in Medical Sciences, 2020)
Background: Nail changes are common in occupational labourers but no studies have been done pertaining to construction site workers. We studied nail changes in labourers working at various construction sites. Methods: 50 labourers of age group 10-65 years and both sexes were enrolled for the study. Changes in nail apparatus were studied by dividing into nail plate, nail bed and nail fold changes. Results: Males outnumbered females in our study. Most of the labourers were in age group of 10-25 years. Most common nail plate changes were Longitudinal ridging and discoloration of nail plate; nail bed were onycholysis, subungual hemorrhage, onycholysis and nail fold changes were absent cuticle and hang nail. Conclusions: Adequate preventive measures are required at construction site workplace to prevent long standing nail sequalae.